Assessment of phytochemical diversity in essential oil composition of eighteen Piper nigrum (L.) accessions from southern India. Issue 6 (2nd November 2021) - Ashokkumar, K.; Vellaikumar, S.; Murugan, M.; Dhanya, M.K.; Karthikeyan, A.; Akilan, M.; Ariharasutharsan, G.; Nimisha, M.; Aiswarya, S.
ABSTRACT: The chemical composition of essential oils isolated from dried berries of eighteen accessions of black pepper ( Piper nigrum L.) from southern India was evaluated by gas chromatography-mass spectrometry analyser. The volatile oil content extracted by hydrodistillation method was ranged from 2.30% to 5.00% (w/w) among the accessions. In total, 41 constituents accounting about 98.3–100% of the total essential oil composition were identified. The main fractions were monoterpene hydrocarbons (60.6–81.2%) followed by sesquiterpene hydrocarbons (16.6–31.1%), oxygenated sesquiterpenes (0.2–3.4%) and oxygenated monoterpenes (0.2–0.9%). The highest content of sabinene and ( E )-β-caryophyllene was obtained from the accessions Irumbirakki and ACC53, respectively. The present study revealed the existence of a new essential oils/chemotypes (safrole and β-ylangene) of the black pepper was not described before from southern India. The major constituents of black pepper essential oil (BPEO) can be utilized in the food, perfumery, aroma and pharmaceutical industries.